Optimized computation method for real-time holographic formation of color images - Makowski, Michał; Ducin, Izabela; Kakarenko, Karol; Kowalczyk, Adam; Bieda, Marcin; Suszek, Jarosław (Photonics Letters of Poland, 2014)
A simple method of decreasing the calculation time of CGH for lensless Fourier holograms is presented. The proposed method takes advantage of the fact that modern displays are rectangular with high image proportion ratio of 16:9 or even higher. The CGH were calculated on the matrix of 512 x 1024 points. The use of small rectangular calculation matrices allowed three times fasters calculation with sustained contrast and noise ratio and greatly improved resolution. Full Text: PDF References M. Makowski, I. Ducin, K. Kakarenko, J. Suszek, M. Sypek, and A. Kolodziejczyk, "Simple holographic projection in color," Opt. Express 20, 25130-25136 (2012). CrossRef M. Makowski, A. Siemion, I. Ducin, K. Kakarenko, M. Sypek, A.M Siemion, J. Suszek, D. Wojnowski, Z. Jaroszewicz, A. Kolodziejczyk, "Complex light modulation for lensless image projection", Chin. Opt. Lett. 9, 120008 (2011). CrossRef M. Makowski, I. Ducin, M. Sypek, A. Siemion, A. Siemion, J. Suszek, and A. Kolodziejczyk, "Color image projection based on Fourier holograms", Opt. Lett. 35, 1227-1229 (2010). CrossRef M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation," Opt. Express 21, 29205-29216 (2013). CrossRef A. Shiraki, N. Takada, M. Niwa, Y. Ichihashi, T. Shimobaba, N. Masuda, and T. Ito, "Simplified electroholographic color reconstruction system using graphics processing unit and liquid crystal display projector," Opt. Exp. 17, 16038-16045 (2009). CrossRef T. Shimobaba, Y. Sato, J. Miura, M. Takenouchi, and T. Ito, "Real-time digital holographic microscopy using the graphic processing unit," Opt. Express 16, 11776-11781 (2008). CrossRef < T. Shimobaba, T. Ito, N. Masuda, Y. Ichihashi, and N. Takada, "Fast calculation of computer-generated-hologram on AMD HD5000 series GPU and OpenCL," Opt. Express 18, 9955-9960 (2010). CrossRef R. W. Gerchberg, and W. O. Saxton, "A practical algorithm for the determination of phase from image and diffraction plane pictures", Optik (Stuttg.) 35, 237–246 (1972). A. Czerwiński, K. Kakarenko, M. Sypek, M. Makowski, I. Ducin, J. Suszek, A. Kolodziejczyk, J. Bomba, "Modeling of the optical system illuminated by quasi-monochromatic spatially incoherent light: New numerical approach", Opt. Letters 37, 4723-4 (2012). CrossRef